2017
DOI: 10.1002/2016ja023646
|View full text |Cite
|
Sign up to set email alerts
|

Transition from global to local control of dayside reconnection from ionospheric‐sourced mass loading

Abstract: We have conducted a series of controlled numerical simulations to investigate the response of dayside reconnection to idealized, ionosphere‐sourced mass loading processes to determine whether they affect the integrated dayside reconnection rate. Our simulation results show that the coupled solar wind‐magnetosphere system may exhibit both local and global control behaviors depending on the amount of mass loading. With a small amount of mass loading, the changes in local reconnection rate affects magnetosheath p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 63 publications
1
26
2
Order By: Relevance
“…In either case, it is possible to create simulations with a mesoscale and turbulent structure that a constant resistivity would not show. It is also worth noting that the local reconnection rate in these models is the same as fine-scaled Hall or PIC results, which is approximately 0.1* v in * B of the inflow region, as shown by many previous studies ( 34 , 55 , 56 ), suggesting that the code is simulating the large-scale configuration of the reconnection process, in terms of the rate of reconnection, reasonably well through the conservation of mass, momentum, and magnetic flux.…”
Section: Methodssupporting
confidence: 79%
See 1 more Smart Citation
“…In either case, it is possible to create simulations with a mesoscale and turbulent structure that a constant resistivity would not show. It is also worth noting that the local reconnection rate in these models is the same as fine-scaled Hall or PIC results, which is approximately 0.1* v in * B of the inflow region, as shown by many previous studies ( 34 , 55 , 56 ), suggesting that the code is simulating the large-scale configuration of the reconnection process, in terms of the rate of reconnection, reasonably well through the conservation of mass, momentum, and magnetic flux.…”
Section: Methodssupporting
confidence: 79%
“…This practically universal scaling indicates that the reconnection rate is not caused by changes in numerical dissipation and that the numerical resistivity is simulating large-scale aspects of reconnection appropriately ( 34 ). It has also been shown that the global rate of dayside reconnection in the magnetosphere is controlled by upstream conditions in the global simulation model rather than the grid resolution of the simulation ( 55 ).…”
Section: Methodsmentioning
confidence: 99%
“…The reconnection electric field is typically of the order of 0.1 vABin, where vA and Bin are the Alfvén speed and magnetic field strength in the inflow region, respectively, indicating that Lyon‐Fedder‐Mobarry‐simulated reconnection is Petschek like (Ouellette et al, , ). Zhang et al (, ) have also shown that the rate of reconnection in the magnetosphere is controlled by the solar wind conditions and electrodynamic coupling through the ionosphere rather than the size of the computational cells.…”
Section: Simulation Informationmentioning
confidence: 99%
“…The rate of reconnection is constrained by a Petschek‐like inflow condition to be a fraction (≈0.1) of the Alfvén speed in the inflow. Details about the properties of magnetic reconnection in the code can be found in Ouellette et al () and in the supporting information of Zhang et al ().…”
Section: Simulation Informationmentioning
confidence: 99%